2016
DOI: 10.1038/srep29458
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in health, diet and weaning patterns amongst the first Neolithic farmers of central Europe

Abstract: Across much of central Europe, the Linearbandkeramik (LBK) represents the first Neolithic communities. Arising in Transdanubia around 5500 cal. BC the LBK spread west to the Rhine within two to three hundred years, carrying elements of a mixed agricultural economy and a relatively homogeneous material culture. Colonisation of new regions during this progress would have required economic adaptations to varied ecological conditions within the landscape. This paper investigates whether such adaptation at a local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Radiocarbon and stable isotope data of the individuals from Brunn am Gebirge site 2, as well as mean stable isotope values (± SD) for European inland Mesolithic (EIM) and European inland Neolithic (EIN)46 , central European LBK45 , and Anatolian Neolithic (AN)9 . Radiocarbon dates for Individuals 2 and 4 (ETH-14827 and ETH-11150) are from 20 .…”
mentioning
confidence: 99%
“…Radiocarbon and stable isotope data of the individuals from Brunn am Gebirge site 2, as well as mean stable isotope values (± SD) for European inland Mesolithic (EIM) and European inland Neolithic (EIN)46 , central European LBK45 , and Anatolian Neolithic (AN)9 . Radiocarbon dates for Individuals 2 and 4 (ETH-14827 and ETH-11150) are from 20 .…”
mentioning
confidence: 99%
“…Cribra orbitalia is commonly ascribed to nutritional deficiency, typically of iron or vitamin B12, resulting from malnutrition or undernutrition or insufficient uptake of such nutrients from a sufficient diet due to the body's natural defence against chronic diarrhoeal disease and parasitic infections commonly associated with childhood diseases (Walker, Bathurst, Richman, Gjerdrum, & Andrushko, ). LEHs are commonly used as a non‐specific physiological response to extrinsic environmental stressors such as disease or nutritional deficiency (Ash et al, ). Defects form on the area of the crown developing at the time the disruption occurs, therefore, reflecting non‐specific early‐life stress episodes (Ogden, Pinhasi, & White, ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have identified that within hierarchically ranked societies, selective distribution of resources determined by social position and status generates variations in physiological stress, which in turn impact upon the physical development and susceptibility to infectious and deficiency diseases of individuals within that society (Bennike, Lewis, Schutkowski, & Valentin, 2005;Goodman, Brooke-Thomas, Swedlund, & Armelagos, 1988;Goodman & Martin, 2002;Peck, 2013;Temple & Goodman, 2014). However, research is increasingly demonstrating multifaceted influences that stimulate the expression of biological and physiological stress upon the skeleton, including differential fertility (Kinaston, Roberts, Buckley, & Oxenham, 2016), epigenetic inertia (Klaus, 2014), social practices such as weaning (Ash, Francken, Pap, Tvrdý, Wahl, & Pinhasi 2016), social and economic change (King, Humphrey, & Hillson, 2005), and varying day-to-day physical activities experienced by different social, occupational, or gender groups (Robb et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Enamel hypoplasia is linked to celiac disease in some patients (Smith and Miller 1979;Wierink et al 2007) but as a non-specific stress indicator. It is also linked to environmental and societal stressors such as food shortage (Geber 2014), weaning (Ash et al 2016) and birth weight (Nelson et al 2013). Enamel hypoplasia can also be a hereditary condition (Robinson, Miller, and Worth1966).…”
Section: Celiac Disease Inferred From Pathological Morphologymentioning
confidence: 99%